As artes na educação médica: revisão sistemática da literatura - Mairot, Lucia Trindade da Silva (2018)
Introduction: The introduction of the arts into the medical curriculum has aroused increasing interest since they present unique qualities that can aid in the development of the social aspects of medical practice, offering new and distinctive ways of exploring knowledge and professional identity. Objective: To evaluate the effectiveness of the use of the arts in the medical curriculum, through a bibliographical review. Methodology: The Lilacs, Scielo, PubMed and ERIC databases were searched for published articles on studies that attempted to evaluate the effectiveness of an arts-based approach in undergraduate medical education. Other articles were identified through active search. The following descriptors (Art or visual arts or paintings or literature or narrative or poetry or theare ormovies or films or cinema) AND (Medical education or medical student or medical curriculum) were used. We included only the articles whose study was conducted with medical students and whose effectiveness of the intervention was evaluated by comparison between groups (quantitative studies) or by medical student satisfaction by questionnaire (qualitative studies). We excluded articles that addressed the use of art in patients and professionals from other health areas, as well as articles describing the importance of art or those that did not describe the intervention used. The selected articles were read in full in order to identify the type of art used in the intervention, the author, the sample, the methodology and the conclusion about the reported activity. Results: A total of 28 articles were included in the study, distributed according to the type of art used: (n = 16) visual arts; (n = 6) literature; (n = 3) theater; (n = 3) cinema. The arts-sensitive educational skills reported in the studies evaluated were: Skills diagnostic observation, teamwork, and reflection and argumentation; facilitating cognitive learning; humanistic aspects of medicine (empathy / patient medical relationship); professionalism. Some studies state that arts-based interventions are effective at changing attitudes; however, they did not define how this success was measured. No study considers the effects on behavior. Evidence for the use of arts-based interventions to promote diagnostic observation skills has been shown to be stronger. However, its effect on other clinical skills has not been studied. Conclusion: Art can be a strategy to facilitate learning, since it helps the student to deal with the complexity of the human being and human health. This broader understanding of health and illness can lead to improved physician-patient relationships in clinical practice. However, due to the qualitative nature of most of the studies, based mainly on the student's opinion of the changes in their attitudes, the effectiveness of the interventions have not always been effectively demonstrated.